Islamic Studies Methodological Reform: Answering the Challenges of Globalization and Intellectual Stagnation - Rumiati, Rumiati; Papriono, Andika; Nursalim, Eko (IJoIS: Indonesian Journal of Islamic Studies, 2025)
Islamic Studies is a multidimensional academic discipline that encompasses not only theological and normative aspects, but also historical, social, cultural, and legal dimensions. Understanding Islam requires a systematic, rational, and scientific methodology to enable an in-depth and contextual analysis of its teachings. This article aims to outline the basic concepts of methodology in Islamic Studies, its scope, and both classical and contemporary approaches. Using a qualitative method through literature review, the article explores the paradigm shift in Islamic scholarship—from a predominantly theological-normative approach to an integrated framework that includes historical, sociological, anthropological, and critical hermeneutical perspectives. The authors also highlight the crucial role of methodology in addressing the challenges of globalization, secularism, and intellectual stagnation among Muslims. Reformist ideas by modern thinkers such as Mohammed Arkoun and Ibrahim M. Abu Rabi offer significant contributions in promoting a more inclusive, contextual, and interdisciplinary understanding of Islam. Therefore, the methodology of Islamic Studies plays a vital role in enhancing scholarly quality and ensuring the relevance of Islamic teachings in contemporary societal dynamics.